Properties of Ag-doped mesoporous bioactive glass coatings on 3D printed pure titanium bone scaffolds - CHEN Qian; ZHAO Xueyang; YOU Deqiang; ZENG Rong; YU Zhentao; LI Wei; WANG Xiaojian (Cailiao gongcheng, 2022)
Infection after surgery is one of the common and most challenging clinical problems, and the development of new antibacterial coating is an effective strategy to solve this problem, which has important scientific and social significance. A bioactive coating with antibacterial function was prepared on the surface of a 3D printed porous titanium bone scaffold. It is discovered that silver (Ag) exists in the coating as a simple substance. As the Ag content increases (0%, 0.5%, 1%, 1.5%, mole fraction), the specific surface area of the mesoporous coating is decreased from 377.6 m2/g to 363.35 m2/g. In vitro mineralization results show that with the increase of Ag content, the apatite inducing ability is decreased slightly. At the same time, the antibacterial test demonstrates that the addition of silver markedly enhances the antibacterial performance of the scaffolds. Adding a small amount of silver (0.5%) can achieve 100% antibacterial rate. The MC3T3-E1 cells are cultured with the scaffolds for 1, 3 and 7 days, and it is found that the Ag-doped MBG coatings have good cyto-compatibility, and the addition of a small amount of silver can promote the proliferation of MC3T3-E1 cells. A simple dipping and pulling method was used to apply the Ag-doped MBG coating to the complex 3D printed titanium scaffolds with complex topological structure. The mineralization performance, bactericidal performance and cellular compatibility of the scaffold are significantly improved, providing a new idea for the further development of multifunctional bone implant scaffold.